Le cartel des arts. Enjeux d’histoire entre assignations ethnographiques et présentations muséales - Claire Bosc-Tiessé (Afriques)
Reconsidering the course of Marcel Griaule’s Ethiopian research, visiting the musée du quai Branly, the author examines the explicit and implicit presuppositions of discourse as well as of the museum’s itinerary, through the analysis of labels and the organization of the museum. She investigates the choices of ethnology and museology in the 1920s and 1930s and their posterity up to the present day, tracing the history of the description of objects, from the cards filled out during fieldwork to the compilation of data for online databases. She thus reassesses the way knowledge about African objects has been established and disseminated. Above all, she highlights the biases of knowledge as well as their ramifications for the understanding of societies, the development of identities, and their possible political uses.